2/x+3/x-3+5/2x=0

Simple and best practice solution for 2/x+3/x-3+5/2x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/x+3/x-3+5/2x=0 equation:



2/x+3/x-3+5/2x=0
Domain of the equation: x!=0
x∈R
Domain of the equation: 2x!=0
x!=0/2
x!=0
x∈R
We calculate fractions
(6x+2)/2x^2+5x/2x^2-3=0
We multiply all the terms by the denominator
(6x+2)+5x-3*2x^2=0
We add all the numbers together, and all the variables
5x+(6x+2)-3*2x^2=0
Wy multiply elements
-6x^2+5x+(6x+2)=0
We get rid of parentheses
-6x^2+5x+6x+2=0
We add all the numbers together, and all the variables
-6x^2+11x+2=0
a = -6; b = 11; c = +2;
Δ = b2-4ac
Δ = 112-4·(-6)·2
Δ = 169
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{169}=13$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(11)-13}{2*-6}=\frac{-24}{-12} =+2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(11)+13}{2*-6}=\frac{2}{-12} =-1/6 $

See similar equations:

| 3y2+y-4=0 | | 4(3x2+2)-9=8x2+7 | | 80-2x=34x= | | 2p/4=28 | | 5x/2-3=6x+3 | | 2x+33=4(x+3) | | -5x+19=-2x+1 | | 10(30x+2)=70 | | 5x/2-3=6(x+1/2) | | (e/5)-4=-3 | | 2(x-3)^2-10=22 | | n/2-1/3=1/6 | | 2a+3=3a-1 | | 6x + 4 = 9x + 22 | | 7a(-7a)=0 | | a/3+2=13 | | 7m+4=73 | | 3×(2+3)=x | | x+31+x+20+x=180 | | 10x+3=12x-17 | | 73/4-x=11/2 | | x-0.15=1/4 | | 120+120+120+110+x+(x+10)=720 | | 6n+4=4 | | 82+2x=94+x | | (5x-2)^2/x-3=4-20x+25x^2/24-11x+x^2 | | 6m^2-m-22=0 | | 3y+5=44=13 | | H=3+14t-5t2 | | 9×3^3x+4=9^x | | 3a+2=a-7 | | (-3/2)^12=(-9/16)-2x |

Equations solver categories